DA'WAH BIL HAL ACTIVITIES IN THE FRIDAY BLESSING OF THE TAKMIR MOSQUE ASH SHAFAAH SOURCEAGUNG VILLAGE PESANGGARAN SUB-DISTRICT - aan maulana; maskur (JKaKa:Jurnal Komunikasi dan Konseling Islam, 2026)
Da'wah bil hal is a form of da'wah that is carried out through actions or deeds, not just through words or lectures. In da'wah bil hal, someone invites others to follow the teachings of Islam by showing real examples in everyday life, such as good attitudes, behavior, and good deeds of worship. The formulation of the problems in this study are (1) How are the values of da'wah bil hal applied in the Friday blessing activity program (2) What are the supporting and inhibiting factors of da'wah bil hal strategy. This research uses qualitative research methods where research is used to conduct research on natural object conditions, data collection techniques are carried out by means of trigulation (combined), data analysis is inductive, and research results focus more on generalization. And using purposive sampling techniques with certain considerations means that each subject taken from the population is selected deliberately based on certain goals and considerations. dakwah bil hal in the blessing Friday program at the Asy Syafaah mosque in Sumberagung village. The results of this study indicate that: dakwah bil hal in the activities of Friday blessings at the Asy Syafaah mosque in Sumberagung Pesanggaran runs well and smoothly. The mosque takmir management is assisted by the community around the Asy Syafaah Mosque in carrying out the activities of Friday blessings every Friday prayer always get positive value from the surrounding community. In addition, donors come directly to give alms and participate in this blessed Friday activity.